Microleakage of Composite Resin Restorations Using a Type of Fifth and Two Types of Seventh Generations of Adhesive Systems: A Comparative Study - Mitra Tabari; Samane Gharekhani; Behnaz Esmaeili; Arash Poorsattar Bejeh Mir; Mobina Mollaei; Mona Alimohammadi; Mahmood Haji Ahmadi (Mashhad University of Medical Sciences, 2016)
Introduction: In recent dentin adhesive systems etching of enamel/dentin are achieved simultaneously. The objective was to evaluate the microleakage of composite restorations using Single Bond2 (5th generation), Clearfil S3 Bond and G Bond (7th generation). Methods: Class V cavities were prepared on  45 extracted intact premolars with gingival margins at the cementoenamel junction and they were randomly divided into 3 groups (n=15) based on the type of adhesives: Single Bond2 (5th generation), Clearfil S3 Bond and G Bond (7th generation). After applying the adhesives, the cavities were filled with Z250 composite resin. The occlusal and gingival microleakage was evaluated using 2% basic fuchsin staining technique. Data were analyzed using Kruskal-Wallis and Bonferroni corrected Mann-Whitney U tests. Results: The mean rank of occlusal microleakage exhibited significant differences by comparison of G Bond, Clearfil S3 Bond and Single Bond2 (21.07, 30.67) and 17.27, respectively) (P=0.005). There was a significant difference in gingival microleakage of different bonding agents (34.40, 17.83 and 16.77 for G Bond, Clearfil S3 Bond and Single Bond2, respectively) (P